Impact of Green Logistics Performance on China’s Export Trade to Regional Comprehensive Economic Partnership Countries - Fan, Mingyue; Wu, Zhiying; Qalati, Sikandar Ali; He, Di; Hussain, Rana Yassir (Frontiers in Environmental Science, 2022)
Based on the logistics performance index proposed by the World Bank, this paper uses the entropy method to construct the green logistics performance index and empirically analyzes the impact of the green logistics performance of Regional Comprehensive Economic Partnership (RCEP) countries on China's export trade by using the expanded trade gravity model. The results show that: Green logistics performance of RCEP countries can significantly promote China's export trade to RCEP countries, and various measures to improve green logistics performance have different impacts on China's export trade. The order of influence degree is the efficiency of a customs clearance procedure, the convenience of arranging freight with competitive price, the timeliness of cargo transportation, the ability and quality of logistics service, and the intensity of CO2 and N2O emission. To promote China's export trade, we should give full play to the functions of the customs of various countries and improve the efficiency of regulatory procedures. To establish a dialogue mechanism with RCEP countries, promote the layout of logistics transport routes among RCEP members, and enhance the popularity of green logistics services; Give full play to the positive role of regional economic organizations and mechanisms, and promote green logistics cooperation between RCEP member countries with high and low GLPI; Through logistics planning, logistics policy and advanced low-carbon logistics technology, promote sustainable development of green logistics.